2012
DOI: 10.1002/ejlt.201200112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analytical and sensory lipid oxidation parameters in conventional and high‐oleic rapeseed oil

Abstract: Headspace-solid-phase microextraction-gas chromatography was used to identify in total 55 volatile lipid oxidation compounds in thermally stressed conventional and high-oleic rapeseed oil samples. Out of this profile, 17 volatile compounds with low odor threshold values were selected as target compounds for the assessment of lipid oxidation in rapeseed and high-oleic rapeseed oils. Additionally, other lipid oxidation parameters such as fatty acid composition, peroxide value, anisidine value, and induction time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 23 publications
3
27
0
1
Order By: Relevance
“…The results of fatty acid profiles for seven refined rapeseed oils are in good agreement with those presented by other authors who reported that SAFA, MUFA, and PUFA amounts ranged between 3.4-8.7%, 58.6-75.0%, and 15.4-29.1%, respectively, while 18:1 (58.6-71.8%) was the most dominant fatty acid in the refined rapeseed oils (Fuentes et al, 2013;Petersen et al, 2012;Roszkowska et al, 2015;Szterk et al, 2010).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results of fatty acid profiles for seven refined rapeseed oils are in good agreement with those presented by other authors who reported that SAFA, MUFA, and PUFA amounts ranged between 3.4-8.7%, 58.6-75.0%, and 15.4-29.1%, respectively, while 18:1 (58.6-71.8%) was the most dominant fatty acid in the refined rapeseed oils (Fuentes et al, 2013;Petersen et al, 2012;Roszkowska et al, 2015;Szterk et al, 2010).…”
Section: Resultssupporting
confidence: 91%
“…To the best of our knowledge, sensory analysis has rarely been used to determine the quality of rapeseed oil, although it was proposed for the evaluation of quality of conventional and high-oleic rapeseed oils after the refining and bottling stored under different conditions (Fuentes et al, 2013;Jele n et al, 2007;Malcolmson et al, 1994;Petersen et al, 2012;Warner and Nelsen, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative stability of conventional high-oleic sunflower oil and analytical and sensory lipid oxidation parameters in conventional and high-oleic rapeseed oil were reported by Petersen et al [260,261].…”
Section: Off-flavorsmentioning
confidence: 85%
“…Many reports have confirmed that a diet containing a high n‐6 to n‐3 fatty acids ratio (which in Western diet reaches a ratio approx. 10–20 to 1) increases chronic inflammatory diseases such as non‐alcoholic fatty liver disease, cardiovascular disease, obesity, inflammatory bowel disease, rheumatoid arthritis and Alzheimer's disease . For example, in a recent study, Costa et al showed the rats fed canola oil (in comparison to the same amount of soybean oil with n‐6 to n‐3 ratio of approx.…”
Section: Introductionmentioning
confidence: 99%